Short-Term Penetration beyond Diffusion Spinodal of a Mixture: Interaction of Liquid-Liquid and Liquid-Vapour Transitions; Frontiers in Heat and Mass Transfer; Vol. 23, iss. 3 - Melkikh A. V. Aleksey Veniaminovich; Ryutin S. B. Sergey Borisovich; Antonov D. V. Dmitry Vladimirovich; Skripov P. V. Pavel Vladimirovich (2025, 2025)
Title screen